2015
DOI: 10.3390/g6040394
|View full text |Cite
|
Sign up to set email alerts
|

Framing and Feedback in Social Dilemmas with Partners and Strangers

Abstract: We study framing effects in repeated social dilemmas by comparing payoff-equivalent Give-and Take-framed public goods games under varying matching mechanisms (Partners or Strangers) and levels of feedback (Aggregate or Individual). In the Give-framed game, players contribute to a public good, while in the Take-framed game, players take from an existing public good. The results show Take framing and Individual-level feedback lead to more extreme behavior (free-riding and full cooperation), especially for Partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…We thus expect more extreme behavior in the take frame, that is, that people are more likely to pool at the endpoints of the action space (take everything or take nothing). This is also a pattern that was found in several previous studies investigating framing effects (e.g., Cox and Stoddard 2015;Dufwenberg, Gächter, and Hennig-Schmidt 2011;Fosgaard, Hansen, and Wengström 2014). For our purposes, the important part is that a greater number of people are expected to pool at the zerocontribution endpoint in the take frame, which is a consistent finding across previous studies (e.g., Andreoni 1995;Cox 2015;Khadjavi and Lange 2015;Park 2000).…”
Section: Theoretical Frameworksupporting
confidence: 88%
“…We thus expect more extreme behavior in the take frame, that is, that people are more likely to pool at the endpoints of the action space (take everything or take nothing). This is also a pattern that was found in several previous studies investigating framing effects (e.g., Cox and Stoddard 2015;Dufwenberg, Gächter, and Hennig-Schmidt 2011;Fosgaard, Hansen, and Wengström 2014). For our purposes, the important part is that a greater number of people are expected to pool at the zerocontribution endpoint in the take frame, which is a consistent finding across previous studies (e.g., Andreoni 1995;Cox 2015;Khadjavi and Lange 2015;Park 2000).…”
Section: Theoretical Frameworksupporting
confidence: 88%
“…Frey (1993) provides a theoretical account under which circumstances such monitoring of information on individual contributions might be a good thing for cooperation. Whereas Cox and Stoddard (2015), van der Heijden and Moxnes (1999) and Weimann (1994) find no effect of individual information on contributions, Carpenter (2004) finds that information on individual contributions leads to faster unravelling of cooperation. In particular, he concludes that when subjects learn about the low contributions of others, they try to conform to the observed group's norms of contributing less.…”
Section: Hypothesesmentioning
confidence: 97%
“…Furthermore, Bigoni and Suetens (2012) show that when individual information on both contributions and earnings is present, a negative aggregate effect obtains. Cox and Stoddard (2015) investigate several dimensions including partner/stranger matching, give/take framing and individual/aggregate information about contributions. In their partners-give-individual/aggregate comparison (which is closest to our setting), they find that individual information slightly increases cooperation, but not significantly so.…”
Section: Hypothesesmentioning
confidence: 99%
“…The work in [40] found no effect, whereas in the experiment reported in [41], aggregate level feedback resulted in subjects making higher contributions to the public goods. The work in [42] ran a design varying framing (give vs. take), matching (partners vs. strangers) and feedback (individual vs. aggregate). They found that in a partners setup with the give framing, there was significantly more free-riding with individual feedback compared to aggregate feedback.…”
Section: Summary and Discussionmentioning
confidence: 99%